Urine based screening for asymptomatic/undiagnosed genital chlamydial infection in young people visiting the accident and emergency department is feasible, acceptable, and can be epidemiologically helpful. Issue 3 (1st June 2003) - Aldeen, T; Haghdoost, A; Hay, P
Abstract : Objective: To assess the acceptability and the feasibility of urine based Chlamydia trachomatis screening in asymptomatic young people aged 16–35 years attending an inner city accident and emergency (A&E) department. Design: Cross sectional study. Setting: A&E department in a teaching hospital, in south London, UK. Method: From July to November 2001 a urine based chlamydia screening test was offered to 719 consecutive A&E attendees aged 16–35 years and their companions. Participants were given an information sheet and were asked to complete a demographic and sexual health questionnaire. Following informed consent, eligible participants provided first pass urine specimens. Specimens were tested for C trachomatis using nucleic acid amplification. Results: Of the A&E attendees asked, 76.5% (550/719) agreed to participate. Prevalence of genital chlamydial infection was 4.2% (18/432; 95% confidence interval (CI) 2.5 to 6.6). 12 of the positive participants (66.7%; 95% CI 40.99 to 86.65) were women, of whom seven were Afro-Caribbean. Nine of the chlamydia positive participants (50%; 95% CI 26.0 to 73.9) were aged 25 years. Three of the positive urine specimens were from companions, of whom a total of 143 were screened. All the positive participants were contactable, and were offered treatment. Conclusion: Urine based screening for undiagnosed genital chlamydial infection in the A&E department was acceptable and feasible. The department provides a unique site for screening young patients and companions, men and women.